Synchronization of bidirection multiple neural networks with impulsive coupling control - Yong Wang; Ailong Wu; Biwen Li (Advances in Difference Equations, 2020)
Abstract This paper is devoted to the study of the global synchronization of multiple neural networks (MNNs) via impulsive coupling control. Compared to one-layer neural networks, MNNs have more complex dynamics behavior and greater practical significance. In this paper, two interconnected bidirection MNNs are constructed; for this type of neural network system, each node in their network will be affected by the corresponding node in another network, then the synchronization problem of unidirection MNNs is extended to bidirection MNNs. In order to achieve synchronization of the bidirection MNNs, we adopt the method of impulsive coupling control, and together with the appropriate Lyapunov function, we deduce the relationship of the synchronization error system at the adjacent two impulsive moments, through iteration, and we finally obtain sufficient conditions to realize the global synchronization of the two interconnected bidirection MNNs. We illustrate the effectiveness of the results by simulation.